1999
DOI: 10.1002/(sici)1097-4660(199903)74:3<216::aid-jctb44>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption kinetics of cephalosporin-c on non-ionic polymeric macropore Amberlite XAD-16 resin

Abstract: : The adsorption kinetics of cephalosporin-c (CPC) on non-ionic polymeric macropore Amberlite XAD-16 resin were investigated in a well-stirred tank. The 'half-time' and non-linear methods were used to derive the intraparticle diþ usivities from the experimentally determined adsorption uptake curves. It was found that both pore and solid surface diþ usion processes made signiücant contributions, in parallel, to the intraparticle mass transfer. It was also found that the CPC concentration had an eþ ect on the eþ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
10
0
5
Order By: Relevance
“…The fresh resin was determined to have an epothilone/resin loading capacity of approximately 80 mg/g. This loading capacity is similar to the 125-mg/g saturation loading at the same resin concentration reported by Yang and Pyle [23] in their study of cephalosporin-C binding to fresh XAD-16 resin. The M. xanthus spent resin has a saturation capacity which is approximately 20% lower than the fresh resin (63 mg/g), while the spent resin from the S. cellulosum cultivation has a saturation capacity approximately 50% lower than the fresh resin (41 mg/g).…”
Section: Fouling Of Product Adsorption Resin During a Microbial Cultimentioning
confidence: 99%
See 1 more Smart Citation
“…The fresh resin was determined to have an epothilone/resin loading capacity of approximately 80 mg/g. This loading capacity is similar to the 125-mg/g saturation loading at the same resin concentration reported by Yang and Pyle [23] in their study of cephalosporin-C binding to fresh XAD-16 resin. The M. xanthus spent resin has a saturation capacity which is approximately 20% lower than the fresh resin (63 mg/g), while the spent resin from the S. cellulosum cultivation has a saturation capacity approximately 50% lower than the fresh resin (41 mg/g).…”
Section: Fouling Of Product Adsorption Resin During a Microbial Cultimentioning
confidence: 99%
“…There is still excess epothilone binding capacity on both types of spent resins, but the reduction in their binding capacities will result in a decrease in the capture rate of further product. It is also possible that a number of the pores in these spent resin beads have become plugged with cells or other matter, decreasing the pore diffusivity rate of the resin and its contribution to the overall binding rate of the epothilone [23]. This decreased capture rate could then result in an increase in the unbound concentration of epothilone D, possibly leading to product repression and enhanced product degradation rates.…”
Section: Fouling Of Product Adsorption Resin During a Microbial Cultimentioning
confidence: 99%
“…They fitted the effective Sherwood number employed by the agitation method against the experiments. Yang et al 12 identified the significance of pore and surface diffusions and estimated the values by the nonlinear regression and "the half-time" methods. However, the diffusion coefficient needs to be further simplified in engineering application.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The intraparticle mass-transfer resistance is often dominant compared with external processes, especially when the particle size is relatively large (e.g. 0.3-1.0 mm) (Yang and Pyle 1999;Ma et al 1996). An understanding of the significance of diffusion processes and accurate estimates of the diffusivities within the adsorbent particles are both fundamental for modelling adsorption processes.…”
Section: Diffusion-controlled Kinetic Modelsmentioning
confidence: 99%